Preparation and properties of iPP hollow fiber membranes for air gap membrane distillation. Issue 50 (26th October 2016) - Wang, Juan; He, Qingfeng; Zhao, Yajing; Li, Pingli; Chang, Heying
Abstract: Three different thickness isotactic polypropylene (iPP) hollow fiber membranes were prepared for air gap membrane distillation (AGMD) via thermally induced phase separation (TIPS) with cosolvent di-n-butyl phthalate and dioctyl phthalate. A study was carried out to investigate the effect of membrane thickness on the water flux and mechanical properties of the membranes. The ratio of membrane thickness to membrane inner diameter was constant at 0.2. Three relevant AGMD modules were fabricated. During AGMD of 6 wt% salt solution, the influence of inlet temperature of cold brine feed ( T 1 ), membrane thickness on permeate water flux ( J D ), gained output ratio (GOR), and thermal efficiency (TE) was experimentally investigated. The maximum J D could reach 6.62 kg/m 2  h and the maximum GOR could reach 6.95, respectively. Furthermore, the maximum TE was 89.42% which was much higher than that of traditional membrane distillation modules. The results demonstrated that the prepared iPP hollow fiber membrane by TIPS method would be of great potential to be utilized in AGMD process for desalination.